2017
DOI: 10.1007/s00167-017-4553-3
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty using ultra-congruent inserts can provide similar stability and function compared with cruciate-retaining total knee arthroplasty

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 23 publications
1
33
0
1
Order By: Relevance
“…However, in their case they did not report any statistically significant differences in AP laxities between implant designs (except at 0°). Song et al 7 reported total AP laxity of the CR and UC knees in flexion to be 6.8 ± 3.5 mm and 7.5 ± 2.3 mm, respectively, but significant differences. Both previous studies reported larger VV laxities than what was measured in the current study, however, a similar outcome was reported (no effect due to bearing design).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…However, in their case they did not report any statistically significant differences in AP laxities between implant designs (except at 0°). Song et al 7 reported total AP laxity of the CR and UC knees in flexion to be 6.8 ± 3.5 mm and 7.5 ± 2.3 mm, respectively, but significant differences. Both previous studies reported larger VV laxities than what was measured in the current study, however, a similar outcome was reported (no effect due to bearing design).…”
Section: Discussionmentioning
confidence: 97%
“…In terms of stability, at least two previous studies compared the AP and VV laxity of CR and “ultra‐congruent” (UC) TKR in patients, but for a different TKR system intra‐operatively using a navigation system. Table compares the results of Lützner et al with the current study, in terms of overall AP and VV laxities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations